Strategi Segmenting, Targeting dan Positioning Pemasaran Beras Merah Organik Jatiluwih Bali di Provinsi Bali - NI PUTU AYU YULIA DEWI; MADE ANTARA; I KETUT RANTAU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Segmenting, Targeting, and Positioning Strategies of Marketing JatiluwihOrganic Brown Rice in Bali Province A company cannot serve all consumers in a vast market. Therefore, if the companywishes to be in the market and win a competition, it must seek a strategy that canunderstand consumers and competitors. This study aimed to determine the marketsegment (segmenting), target market (targeting) and market position (positioning) oforganic red rice products of Jatiluwih Bali. The technique of determining samplesused accidental non-probabilitiy random sampling method. Segmenting and targetingwere done using cluster analysis and crosstab analysis tools. Positioning used Multidimensional scaling and Corespondence analysis. The results of this study showedthat there were 3 segments, with percentage of Segment-1 (49%), Segment-2 (31%)and Segment-3 (20%). Based on the market appeal, potential target market wassegment-3. Product positioning based on MDS analysis tool, Jatiluwih rice productwas not in any quadrant, so it showed no resemblance to the competitor's product.Positioning based on CA analysis, organic red rice products Jatiluwih Bali hadadvantages in health attributes, packaging and aroma. Suggestions that can be madeare that the company should implement strategies to increase sales by maintaining orincreasing the attributes of excellence, increasing price discounts and maintainingquality, developing promotional activities and diversification of processed red riceproducts.